Class, race, gender and crime: the social realities of justice in America - Barak, Gregg (Rowman & Littlefield, 2010)
Introduction -- Understanding class : wealth, inequality & corporate power -- Understanding race : social constructions and white privilege -- Understanding gender : male privilege & the 51% minority -- Class, race & gender : intersections & integrations -- Criminology & criminal justice -- Law making, criminal law & the administration of justice -- Victimology & victimization -- Law enforcement and criminal adjudication -- Punishment, sentencing & imprisonment -- Conclusion crime, justice & policy